The effect of proteolytic enzymes on hair follicles of transgenic mice expressing the lac Z-protein in cells of the bulge region - Protopapa, Evangelia; Gaissert, Henning A.; Xenakis, A.; Avramiotis, S.; Stavrianeas, N.; Sekeris, C. E.; Schenkel, Johannes; Alonso, Angel (Journal of the European Academy of Dermatology and Venereology, 1999)
OBJECTIVE: To study the effects of proteolytic enzymes on mice hair follicles, particularly on cells of the bulge area regarded as follicle stem cells. - BACKGROUND: Previous application by iontophoresis of proteolytic enzymes on guinea pig skin resulted in degenerative effects on hair follicles and the hypothesis was proposed that some of the affected cells could be stem cells. - METHODS: To mark putative stem cells transgenic mice were produced carrying the lac-Z gene fused to the Upstream Regulatory Region (URR) of Human Papilloma Virus 11 (HPV11), as they express this gene specifically in the cells of the bulge area. Chymotrypsin and papain were applied on skin by iontophoresis, trypsin in the form of liposomes. - RESULTS: Enzyme application, both by electrophoresis and as liposomes, led to intense degenerative effects of the hair follicle, such as detachment of the inner root sheath, cystic dilation of the hair shaft and presence of epithelial cells within the lumen. Some of these cells represent hair follicle stem cells expressing beta-galactosidase (beta-gal), having been detached from the bulge area as a result of enzyme treatment, implying impairment of their function.
Published: 29 September 2006
Gesehen am 10.05.2021
Elektronische Reproduktion der Druck-Ausgabe